(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The analysis of clinical, anamnestic and laboratory examination of 80 women with hyperandrogenism syndrome in the first trimester of pregnancy was carried out in order to identify risk factors for reccurent miscarriages. Our data are consistent with the results of other studies that obesity and insulin resistance are risk factors for habitual miscarriage [6, 7]. In this case, possible pathogenetic links are insulin resistance, hyperinsulinemia, hyperandrogenism.